A characterization by the product element orders for some groups. Issue 4 (18th May 2020) - Mousavi, Seyed Farid; Gilani, Alireza; Alaeiyan, Mehdi; Golriz, Maryam
Abstract: Given a finite group G, we denote by ψ′( G ) the integer, where o ( g ) denotes the order of g ϵ G . It was proved by B. Khosravi and M. Baniasad Azad [12] that some finite simple group can be uniquely determined by its product of element orders. In this paper, we characterize Alt(5) × ℤ2 by its order and the product of element orders.